The evaluation of the mitochondrial genomics in Atlantic salmon (Salmo salar) - Mohammad Aghajanpour Ghasemabad; Abolhasan Rezaei (Mitochondrial DNA. Part B. Resources, 2018)
The mitochondrial genomic of Atlantic salmon (Salmo salar) was sequenced and deposited in GenBank accession no. LC012541.1. In this study for the evolutionary analysis of Mtgenomic between S. salar and other salmonid species such as S. t. fario, S.t. trutta and S.t. caspius were conducted by using MEGA Software Version 7. The results showed that there is a major homology between S. salar and other salmonids like S.t. fario and S.t. trutta, and we can see it in showing the close relationship between them.